Stress and coping mechanisms for instructional leaders in the COVID-19 pandemic - Co, Maria Yvon; Alberto, Mercedita (International Journal of Arts, Sciences and Education, 2022)
Education has change over the years and it gone through big transformation since the Covid-19 pandemic started. Teachers and learners adapted through different modalities and technique to continue the quality learning. Instructional leaders faced different challenges and hindrances amidst pandemic that affected their professional and personal lives and developed different coping mechanisms to manage stress. This study aimed to describe and narrate the stress and coping mechanism for public instructional leaders, filled a hole identifying the effective and efficient coping mechanism for instructional leaders, and to offer teaching and non-teaching personnel with necessary resources to assist instructional leaders experiencing stress. The qualitative transcendental phenomenology approach was considered in this study. A phenomenological approach allowed participants to expand on the responses to adequately capture thoughts and feelings through in-depth interview. This design allowed an intensive in-depth study on the shared experiences of a bunch of participants. Six willingly and voluntarily instructional leaders or Master Teacher I from selected public secondary school participated in the study by having an in-depth critical analyzation and with the use of thematic data analysis, ten themes were identified and discussed. Lastly, the stress experiences of the Instructional Leaders (ILs) during the pandemic made them realized that they should always cease the day, model resiliency, and seek for self-improvement. Even amidst pandemic, they learn to be a leader, guide subordinate and have positive mindset.